Radio Access Network Dimensioning for 3G UMTS - Li, Xi.; SpringerLink (Online service) (Wiesbaden : Vieweg+Teubner, 2011)
An important means for improving the cost-efficiency in modern mobile radio networks is to dimension the radio access network carefully. Xi Li presents innovative analytical models and algorithms for the dimensioning of the 3G UMTS Radio Access Network (RAN). The proposed analytical models allow efficient and accurate dimensioning for different evolutions of UMTS radio access technologies. The author validates the analytical models by simulations using developed UMTS system simulation models. All presented analytical dimensioning models are implemented into a commercial dimensioning tool. This dimensioning tool is used to help the 3G UMTS network operators to optimize their network infrastructure in order to reduce network costs while still being able to offer desired Quality of Service.
Keywords: Computer science; Computer Science; Computer Science, general